The association of circadian rhythms with academic, physical, and cognitive performance: A systematic review - Ikram Sabaoui; Said Lotfi; Mohammed Talbi (Образование и наука, 2024)
Introduction. Biological cycles exist across diverse time spans. Circadian rhythms are the most thoroughly examined and significantly influence individuals. These rhythms in physiological measures are affected by cyclical variations in human actions and surroundings over a 24-hour duration.                Aim. The present research aims to analyse the association of biorhythm factors with performance in students considering research in the field of chronobiology in relation to the educational field.                Research methodology and methods. The present systematic review summarises 34 records treating sleep quality, lifestyle, and circadian preferences in their association with the academic, physical, and cognitive performance of students during their daily life; using a PRISMA model.                Results. The current review paper has cited numerous studies that confirm the significant impact of sleep and circadian preference on a student’s academic, psychomotor, and cognitive performance. These two factors play a crucial role in the rhythmicity of a student’s life.                Scientific novelty. This study introduces a novel interdisciplinary method that applies findings from the study of biological rhythms to education, revealing how these rhythms affect student learning and performance. By merging chronobiology with educational theory, it opens new research paths and enhances our understanding of the relationship between students’ circadian rhythms and their academic, cognitive and physical results, representing a significant progression in how the field of education is linked with chronopsychology.                Practical significance. Educational professionals can use the results obtained to gain a deeper insight into how chronobiological factors may affect student performance, thereby enhancing their comprehension of student productivity and potentially identifying more efficient ways to improve it.